2006
DOI: 10.1073/pnas.0608995103
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of MEK2 and IκB kinase (IKK) activation loop residues by YopJ inhibits signaling

Abstract: To overcome host defenses, bacterial pathogens of the genus Yersinia inject specific effector proteins into colonized mammalian cells. One such virulence factor, YopJ, inhibits the host inflammatory response and induces apoptosis of immune cells by blocking multiple signaling pathways, including the MAPK and NF-B pathways. In this study, we show that YopJ exerts its deleterious effects by catalyzing the acetylation of two serine residues in the activation loop of the MAP kinase kinase, MEK2. This covalent modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
282
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(292 citation statements)
references
References 30 publications
8
282
0
2
Order By: Relevance
“…These three bacterial effector proteins are secreted by a type III secretion system (T3SS) and translocated through the Salmonella or Chlamydia vacuolar membrane into the cytosol. Their mode of action differs from that of YopP/YopJ protein of Yersinia, which acetylates IKKα and IKKβ, thereby preventing phosphorylation of IκB (36,37). Enteropathogenic Escherichia coli (EPEC) also has been shown to prevent the phosphorylation of IκB through the use of two T3SS effectors, NleE and NleB, which interact with the TAK1-IKK A B pathway, albeit in an unknown fashion (38).…”
Section: Discussionmentioning
confidence: 99%
“…These three bacterial effector proteins are secreted by a type III secretion system (T3SS) and translocated through the Salmonella or Chlamydia vacuolar membrane into the cytosol. Their mode of action differs from that of YopP/YopJ protein of Yersinia, which acetylates IKKα and IKKβ, thereby preventing phosphorylation of IκB (36,37). Enteropathogenic Escherichia coli (EPEC) also has been shown to prevent the phosphorylation of IκB through the use of two T3SS effectors, NleE and NleB, which interact with the TAK1-IKK A B pathway, albeit in an unknown fashion (38).…”
Section: Discussionmentioning
confidence: 99%
“…3, C and D), whereas NEDD8-AMC was hydrolyzed by SENP8, used as positive control. Because YopJ was originally suggested to have DUB activity (16), but subsequently shown to be an acetyltransferase (18,19), we also tested our preparation of SseL catalytic domain but detected no acetyltransferase activity (data not shown). Altogether, these data confirm that SseL has an intrinsic and specific DUB activity, and this activity is dependent on cysteine 285.…”
Section: Ssel Is a Deubiquitinating Enzymementioning
confidence: 99%
“…YopJ is homologous to CE cysteine proteases and was reported to hydrolyze ubiquitin and SUMO (a ubiquitinlike protein) (15)(16)(17). YopJ was also shown to act as an acetyltransferase that blocks phosphorylation sites on MAPKK6 and IKK␤ kinases implicated in NF-B activation (18,19). The physiological relevance of YopJ in the pathogenic mechanism of Yersinia has been demonstrated in experiments comparing the lethality of wild-type (WT) and YopJ-deficient bacteria (20).…”
mentioning
confidence: 99%
“…In one study, the YopJ homolog, YopP, was shown to inhibit mammalian TAK1; however, no mechanism was identified (11,12). A number of in vitro studies identified the MAP2 kinase family as targets of YopJmediated serine/threonine acetylation (9,10). Through these acetylations, it was argued that YopJ is capable of inhibiting both MAPK (ERK pathway in particular) and NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In this role, YopJ acetylates serines and threonines on various mitogen-activated protein kinase kinases (MAP2Ks). This acetylation blocks the phosphorylation and activation of these kinases, thus neutralizing these signaling pathways (9,10). Interestingly, the Yersinia enterocolitica homolog, YopP, has been shown to inactivate the mammalian MAP3 kinase, hTAK1; however, the mechanism of suppression is not yet established (11,12).…”
Section: Drosophila Immunity | Innate Immunitymentioning
confidence: 99%